Efficacy and safety of radiofrequency ablation for hypertrophic obstructive cardiomyopathy: A systematic review and meta‐analysis - Yang, Haonan; Yang, Yuan; Xue, Yuzhou; Luo, Suxin (Clinical cardiology (Mahwah, N.J.), 2020)
Background Although radiofrequency ablation is widely used in the treatment of arrhythmias, its role in septal reduction therapy of hypertrophic obstructive cardiomyopathy (HOCM) is unclear. This meta‐analysis aimed to assess the efficacy and safety of radiofrequency septal ablation for HOCM. Hypothesis Radiofrequency septal ablation is effective and safe for relieving obstruction and improving exercise capacity in patients with HOCM. Methods A systematic review of eligible studies that reported outcomes of patients with HOCM who underwent radiofrequency septal ablation was performed using PubMed, Embase, Cochrane, ProQuest, Scopus, ScienceDirect, and Web of Science database. Pooled estimates were calculated using random‐effects meta‐analysis. Methodological quality was assessed using the Newcastle‐Ottawa scale. Publication bias and sensitivity analyses were also performed. Results Eight studies with 91 patients (mean follow‐up 11.6 months) were included. The left ventricular outflow tract (LVOT) gradient at rest decreased significantly after radiofrequency septal ablation (pooled reduction: −58.8 mmHg; 95% confidence interval [CI] −64.3 to −53.5). A reduction was also found in the provoked LVOT gradient with a pooled reduction of −97.6 mmHg (95% CI: −124.4 to −87.1). An improvement of the New York Heart Association classification (mean: −1.4; 95% CI: −1.6 to −1.2) was found during follow‐up. The change in septal thickness was minimal and not statistically significant. Two procedure‐related deaths were documented, and complete heart block occurred in eight patients. Conclusions Radiofrequency septal ablation is effective and safe for relieving LVOT obstruction and improving exercise capacity in patients with HOCM.